Penggunaan Media Youtube dalam Meningkatkan Hasil Belajar Materi Zakat dan Hikmahnya di Madrasah Aliyah Miftahul Ulum Weding Demak - Subqi, Imam (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2021)
This study aims to determine the activeness and learning outcomes of students on zakat material and its wisdom through youtube media at Madrasah Aliyah Miftahul Ulum Weding Demak. The research used is a classroom action research approach. The results showed that based on the results of the last recap, it appears that the learning outcomes from cycle I to cycle III have increased. In the first cycle the average results obtained were 66.36, increasing to 73.60 or 7.24% in the second cycle. In the third cycle the average value reached 76.78, an increase from the second cycle of 3.18%. From these data, it can be concluded that with the optimal application of youtube media in fiqh learning for class X Miftahul Ulum Weding Demak students can improve learning outcomes.